Evaluasi Kebijakan Sistem Zonasi Pada Penerimaan Peserta Didik Baru Jenjang Pendidikan Dasar Sekolah Menengah Pertama - Vika Ardianti; Achmad Supriyanto (Universitas Pendidikan Indonesia, 2021)
This study aims to understand the extent which Zoning System Policy at the Junior High School Elementary Education level is running. The method in this study uses a Literature Study that utilizes national journals from various sources, one of which is Google Scholar. The results of the study show that the zoning system has an impact on several schools that do not get students so that they cannot meet the predetermined quota. The zoning system is a new policy issued by the government in order to overcome educational problems in Indonesia, one of which is equal distribution of education. The zoning system is one of the paths of the PPDB system by using the measurement of the radius and distance from the student's house to the destination school. In its implementation, the zoning system policy still raises pros and cons to community groups. In addition, the zoning system also has an impact on 5 aspects including aspects of effectiveness, adequacy, equity, responsiveness, and accuracy. However, the process of implementing the zoning system is considered quite good, but it is still necessary to pay attention and improve several things so that the objectives of the zoning system policy can be realized.